2010
DOI: 10.4300/jgme-d-09-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Knowledge Among Resident Specialties: Lecture-Based Training and the OUCH Card to Treat Children's Pain

Abstract: There are unique concerns for residents and fellows treating hospitalized children in pain. Some children cannot necessarily communicate their pain, 1,2 and the dosages for children differ dramatically by age and weight.3 Finally, because of a fear of adverse effects, the undertreatment of pain (ie, giving too little medicine) has been reported. 4,5 Lapses in the treatment of children's pain have been attributed, in part, to the following: systematic and logistical barriers within institutions providing pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Notably, pediatric residents and attending physicians have noted the need for increased training in pediatric pain management. 14 Siegler et al found that residents were more likely than more experienced physicians to overprescribe opioids in order relieve a patient's pain. 15 The American Academy of Pediatrics, in partnership with the Providers' Clinical Support System for Opioid Therapies, provides access to training and mentoring in adolescent opioid use.…”
Section: How Education For Physicians Can Address This Complex Issuementioning
confidence: 99%
“…Notably, pediatric residents and attending physicians have noted the need for increased training in pediatric pain management. 14 Siegler et al found that residents were more likely than more experienced physicians to overprescribe opioids in order relieve a patient's pain. 15 The American Academy of Pediatrics, in partnership with the Providers' Clinical Support System for Opioid Therapies, provides access to training and mentoring in adolescent opioid use.…”
Section: How Education For Physicians Can Address This Complex Issuementioning
confidence: 99%
“…[11][12][13] Most of these curricula exclude specific instruction in pain control and focus on opioid abuse rather than on appropriate dosing and management of opioids to treat pain. Few published interventions specifically address pain management in children, [14][15][16][17][18] and most require attendance at real-time lectures or workshops. The ongoing opioid epidemic may further limit attention to, and education of trainees in, treating pain.…”
mentioning
confidence: 99%